2018
DOI: 10.1177/2156759x19834293
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Management Competencies for School Counselors: A Delphi Study

Abstract: The school counseling core curriculum is an essential element of a comprehensive program. School counselors need to be proficient in classroom management to successfully implement this intervention, yet few recent empirical investigations of school counselors' classroom management knowledge and skills exist. We conducted a Delphi study with school counseling classroom management experts to create a consensus list of competencies associated with effective classroom management for school counselors. We provide i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 44 publications
(100 reference statements)
0
17
0
1
Order By: Relevance
“…Elementary school counselors are encouraged to provide classroom instruction as part of their comprehensive programs (ASCA, 2019), and research has addressed some topics related to school counseling classroom lessons (e.g., Akos et al, 2007; Buchanan et al, 2017; Geltner et al, 2011; Runyan et al, 2019). However, Ziomek-Daigle et al (2016) identified a dearth of literature on elementary school counseling in general, and we found no published research examining school counselor experiences teaching classroom lessons.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Elementary school counselors are encouraged to provide classroom instruction as part of their comprehensive programs (ASCA, 2019), and research has addressed some topics related to school counseling classroom lessons (e.g., Akos et al, 2007; Buchanan et al, 2017; Geltner et al, 2011; Runyan et al, 2019). However, Ziomek-Daigle et al (2016) identified a dearth of literature on elementary school counseling in general, and we found no published research examining school counselor experiences teaching classroom lessons.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Nevertheless, limited research exists related to school counselors teaching classroom lessons in elementary schools. Some scholars have addressed skill-related concerns such as classroom management (Buchanan et al, 2017;Geltner et al, 2011;Runyan et al, 2019) and lesson development (Akos et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Como metodología de investigación, utilizamos el método Delphi adaptado a las características de nuestros participantes, Si bien el método Delphi se ha utilizado ampliamente en la investigación educativa, estas investigaciones hacen referencia principalmente a la visión del profesor (experto) sobre el tema de estudio (Runya et al, 2018;Calabor et al, 2019;Akar, 2020). En nuestra propuesta adaptamos la técnica Delphi para involucrar a los estudiantes de Auditoría en la identificación de los dilemas éticos a los que deberán hacer frente en su futuro quehacer profesional, y por tanto, no utilizamos un panel de "expertos" propiamente dicho.…”
Section: Introductionunclassified
“…
School counseling classroom lessons provide all K-12 students with Tier 1 preventive supports. Educators use classroom management strategies to best deliver classroom lesson content to K-12 students, although the existing literature for school counselors in particular is sparse (e.g., Goodman-Scott, 2019;Runyan et al, 2019). We describe the creation and validation of the first known assessment on school counseling classroom management: the School Counseling Classroom Management Inventory, resulting in a five-factor model.
…”
mentioning
confidence: 99%